2016
DOI: 10.1111/jai.13042
|View full text |Cite
|
Sign up to set email alerts
|

Catch composition and some other aspects of bottom trawl fishery in Sığacık Bay, central Aegean Sea, eastern Mediterranean

Abstract: The objective of the study was to determine the features of the bottom trawl fishery such as catch composition, catch per unit effort (CPUE) and the discard ratios in the Sı gacık Bay fishery, central Aegean Sea. A commercial trawler conducted trawl operations from October 2008 to April 2009, with a total of 18 trawls in autumn, winter and spring (six hauls per season). In total, 84 species were identified, 47 of which belonged to the bony fishes, while other groups contributed nine (cartilaginous fish), 10 (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Across the Mediterranean Sea, the knowledge on discarding of L. caudatus is scattered and scarce (e.g., Sánchez et al, 2004;Tzanatos et al, 2007;Soykan et al, 2016;Carbonnel and Mallol 2012). The discard rates are affected by gears, target species, fishing ground depth, as well as the request of the local market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the Mediterranean Sea, the knowledge on discarding of L. caudatus is scattered and scarce (e.g., Sánchez et al, 2004;Tzanatos et al, 2007;Soykan et al, 2016;Carbonnel and Mallol 2012). The discard rates are affected by gears, target species, fishing ground depth, as well as the request of the local market.…”
Section: Discussionmentioning
confidence: 99%
“…Tzanatos et al (2007) in the Aegean Sea and Sánchez et al (2004) in the Catalan Sea reported that the whole catch of L. caudatus was discarded by gillnet and by trawlers, respectively. Conversely, Carbonell and Mallol (2012) provided discard rate estimation by trawlers of 7% in Catalonia waters and 100% in Balearic island, while Soykan et al (2016) estimated a discard rate of about 30% in Turkish waters.…”
Section: Discussionmentioning
confidence: 99%
“…JICA (1993) conducted surveys in territorial waters of Turkey as well as in international waters at a depth of 20-500 m. There were 24 and 20 invertebrate species observed in the Northern Aegean Sea and the South Aegean Sea, respectively. Soykan et al (2016) conducted studies in Sığacık Bay (Central Aegean Sea) using a commercial trawler, in which a total of 28 invertebrate species, 10 cephalopods, 13 crustaceans, 4 echinoderms and one porifera were captured. Kallianiotis et al (2000) reported 26 invertebrate species off Heraklion Bay between 50 and 1000 m.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that about 88 cartilaginous species inhabit the Mediterranean Sea (FAOa, 2018;FAOb, 2018), and that 75% of these species are also found in the Aegean Sea (Eronat & Bizsel, 2015). This group contributes a considerable part of by-catch in Turkish trawl fisheries (Gurbet, Akyol, Yalçın, & Özaydın, 2013;Soykan, Akgül, & Kınacıgil, 2016). According to Eronat and Özaydın (2011) at least 15 chondrichthyan species are regularly presented in the fishery of study area.…”
Section: Introductionmentioning
confidence: 98%